RETRO-MAPPING: A New Approach to Activation Mapping in Persistent Atrial Fibrillation Reveals Evidence of Spatiotemporal Stability. (17th May 2021) - Mann, Ian; Linton, Nick W.F.; Coyle, Clare; Howard, James P.; Fudge, Michael; Lim, Elaine; Qureshi, Norman; Koa-Wing, Michael; Whinnett, Zachary; Lim, Phang Boon; Ng, Fu Siong; Peters, Nicholas S.; et al.
Abstract : Background: The mechanisms underlying atrial fibrillation (AF) remain controversial. We developed Representation of Electrical Tracking or Origin-Mapping to characterize activation wavefronts by direction and uniformity, accumulating data as an orbital plot and analyzed as frequency histograms. We applied this technique to patients undergoing AF ablation to determine if AF activation is random. Methods: Patients undergoing persistent AF ablation were recruited, and an AFocusII was positioned at multiple left atrial locations and kept steady for 1 minute to collect electrograms. The AFocusII was returned to the original site and position after >10 minutes for a repeat 1-minute data collection. Data were exported to custom Representation of Electrical Tracking or Origin-Mapping software, and 30 seconds consecutive time windows at each location were studied using frequency histograms of wavefronts. R50 (the range in degrees containing 50% of the total activation) was used as a method to enable statistical comparisons of activation patterns. Electrogram characterization into categories of complex fractionated atrial electrograms by Ensite Precision was subjected to similar analysis. Results: Consecutive 30 seconds segments were studied at 161 locations in 18 pts. Mean overlap between frequency histograms was 79.5%±7.7 (95% CI, 78.3–80.7). Nine patients underwent delayed mapping at the same location, and mean overlap between the first 30 seconds and >10 minute interval was 73%±11.8 and 71.9%±13.6 for consecutive 30-second segments. Stability was confirmed using R50 (Bland-Altman mean difference: 0.87°; limits of agreement: −34.0 to 36.0; r =0.005; P =0.95). A greater variance in R50 was observed between different locations within a patient than the variance within the same locations (intraclass correlation=0.765; P <0.0001) and similarly for both complex fractionated atrial electrogram and bipolar voltage ( P <0.0001). A larger area containing complex fractionated atrial electrogram (80–120 ms) showed weak positive correlation with increasing R50 ( r =0.36, P <0.001) suggesting a relationship between activation pattern and electrogram characteristics. Conclusions: There appears to be preferential activation patterns during persistent AF indicating spatiotemporal stability. This has important implication to our mechanistic understanding of persistent AF.